SOLIDARITY LETTERS: University project focused on recognizing and promoting mental health at work - Carvalho, Luana Monteiro (2024)
This work explores the influence of affectivity as a way of recognizing teachers’ efforts in an increasingly competitive and stressful academic context. The "Solidarity Letters" Project developed by the State University of Minas Gerais (UEMG) aimed to use means of expressing recognition at work as an element capable of promoting mental health to teachers of law and physical education courses who work at this university. The theoretical precepts come from the clinical-theoretical discipline psychodynamics of work, which dates back to the 1980s and originates in France. To this end, letters written by students from both courses were collected, after immersion in theoretical training in the areas of work psychodynamics and project management. The results of the intervention reinforce that recognition is an important component of promoting quality of life at work. It concludes on the importance of incorporating rituals of recognition and stimulation of affectivity in academic practices, especially for student training in work psychology. This approach not only humanizes the university environment, but has the potential to significantly enrich the teaching and learning process.